AKLIMATISASI PERTUMBUHAN BIBIT ANGGREK CATTLEYA (Orchidaceae cattleya sp) HASIL KULTUR JARINGAN DENGAN PEMBERIAN PUPUK ORGANIK CAIR (POC) - Rahmawati, Eka; Raden, Ince; Mutiah, Mutiah (Jurnal Magrobis, 2017)
The study is aimed to know the effect of liquid organic fertilizer, given toward of orchicidaceae cattleya growth. The study was arranged by complate randomized design: non factorial. By OFL treatment (coconut water and water of rice washing) was repeated three times. The treatmant of (OFL) was consisted of 10 level k0 (Without Liquid Organic Fertilizer), k1 (coconut water 2,5 ml L-1 water), k2 (coconut water 5,0 ml L-1 water), k3 ( coconut water 7,5 ml L-1 water), b4 (water of rice washing 2,5 ml L-1 water), b5 (water of rice washing 5,0 ml L-1 water), b6 (water of rice washing 7,5 ml L-1 water), kb7 (coconut water 2,5 ml L-1 + water of rice washing 5,0 ml L-1 water), kb8 (coconut water 5,0 ml L-1 + water of rice washing 5,0 ml L-1 water), and kb9 (coconut water 7,5 ml L-1 + water of rice washing 7,5 ml L-1 water).The result of this study showed that OFL treatment didnt give an effect to the avarege, number of high plants, and number of leaves at the age of days 25, 35, 45, and 55 after planting period. The unreal effect was on the paremeter of roots number at the age of days 25, 35, 45, and 55 after planting period. Meanwhile, the POC treatmen gave an real effect to the avareg of roots number at the age of days 45 after planting period.Keywords: Growth, Orchid, Liquid organic fertilizer.